Detection of The p53 Gene in Formalin Fixed Tissue Archives by Polymerase Chain Reaction (PCR) Method - Anastasia Elma Wijayanti; Fitria Diniah Janah Sayekti (Biology, Medicine, & Natural Product Chemistry, 2025)
Formalin fixed tissue archives are tissue biopsy results stored in formaldehyde fixative solution for a long time. The p53 gene is one of the genes that suppresses tumor occurrence and maintains genomic stability to prevent cell mutation and plays a role in the DNA regulation cycle and controls cell proliferation. Polymerase Chain Reaction (PCR) is a nucleic acid amplification technique used to denature and denature DNA or RNA using polymerase enzymes to detect the presence of the p53 gene in formalin-fixed tissue archival samples. This study aimed to detect the presence of the p53 gene in formalin-fixed tissue samples. This study used a descriptive research method with a random sampling technique conducted in the anatomical pathology laboratory and the National College of Health Sciences molecular biology laboratory. The samples in this study consisted of 10 samples consisting of 2 normal tissues used as controls and 8 formalin-fixed tissue samples. In this study, the p53 gene was detected in all samples, both normal tissue samples and formalin-fixed tissue samples after electrophoresis and visualized according to the target of 666 bp (base pair). The presence of the p53 gene qualitatively from DNA isolates can still be detected, but the gene expression level cannot be known in this study.